Developmental trajectory of long-lived plasma cells - Koike, Takuya; Ise, Wataru (Frontiers in Immunology, 2025)
Long-lived plasma cells (LLPCs), which continuously secrete antibodies, play a central role in humoral immunity and form the foundation of effective vaccine strategies. The anatomical segregation between the tissues where plasma cells are generated and where they are maintained suggests that both cell-intrinsic and extrinsic factors contribute to their longevity; however, the underlying cellular and molecular mechanisms remain largely unclear. In this review, we summarize recent advances in elucidating the regulation of plasma cell survival at both induction and effector sites. We particularly highlight potential LLPC precursors among newly generated plasma cells in secondary lymphoid tissues, and their subsequent maturation and differentiation into bona fide LLPCs within the bone marrow.